Propuesta de Diseño de Procesos Para el Aseguramiento de la Calidad del Producto en la Elaboración Artesanal del Queso de Hoja, Provincia de Gutiérrez, Boyacá. (2023)
The present project consists of the elaboration of the process design proposal for the assurance of the quality of the product in the artisan elaboration of the cheese from the sheet in the province of Gutiérrez, Boyacá, it contemplates the type of mixed investigation, with descriptive, exploratory approaches. , and applied; descriptive when making an initial diagnosis of the current situation; exploratory as there is little information in the database and use primary data collection instruments; and applied when designing a model that can be used in the agroindustrial sector, which consists of a methodology focused on a preliminary phase in which the sample was identified and calculated, through the collection and analysis of data from leaf cheese manufacturers. artisanal, in the first phase it was characterized and diagnosed through activities, processes, times, personnel and machinery and equipment, the second phase identified and analyzed each of the activities in the manufacturing process oriented to methods, raw material, machinery and equipment, and finally in the third phase where the quality assurance proposal was designed in quality management, measurement points, measurement standards, and quality manuals and procedures.